MAQASID SHARIA VIEW ON THE EFFECT OF MEMORY AND PERCEPTIONS ON BRAND AWARENESS AND THEIR IMPLICATIONS ON FINANCING DECISIONS - Joni Hendra K; Sukiman Sukiman; Sugianto Sugianto; Kurnial Ilahi (Proceeding International Seminar of Islamic Studies, 2022)
This research was conducted at PT Bank Syariah Indonesia (Persero) Tbk Pekan Baru branch, Riau Province. The number of respondents was 150 respondents. They were MSME customers included in the creative economy in Pekanbaru City with current financing status. The sampling method used is accidental sampling. The study intends to know the view of maqasid sharia, the influence of memory and perceptions of creative economy actors on brand awareness, and their implications for financing decisions. The research is done by using SEM model, data processing with PLS 3.0 smart software. The research answers the view of maqasid sharia in the influence of motivation and perception on brand loyalty and its implications for financing decisions for creative economy UMKM customers.Keywords: Memory, Perception, Brand Awareness, Financing Decisions, Maqasid Sharia